Technologies For Developing Innovative Management Competences Of School Educational Leadership Staff In The Professional Training System (Eurasian Journal of Learning and Academic Teaching, 2026)
This article theoretically analyzes the technologies for developing innovative management competencies of managers of preschool educational organizations in the system of advanced training. Within the framework of the study, the content, components and role of the concept of innovative management competencies in the preschool education system were determined. The theoretical foundations of andragogic, competency-based and transformational approaches in the process of advanced training were studied and the possibilities of their application to preschool education leaders were substantiated. As a result of the theoretical analysis, the cognitive, functional, social and metacognitive components of innovative management competencies were distinguished, their interrelationships and significance in the activities of preschool education leaders were revealed. Also, the theoretical and methodological foundations of the development of innovative management competencies in the system of advanced training were formed and relevant scientific proposals were developed.